The Role of the Environment in Increasing the Effectiveness of Communication, Information and Education (KIE) Through the Role Play Method on Knowledge of Preventing Sexual Violence in Middle School Children - Lili Anggraini; Kusuma Ayu Sugiarsih; Lina Rohtiana; Listania Fahrani; Kartika Riyadi Sofci; Lisna Lestari (Jurnal Penelitian Pendidikan IPA, 2024)
This study evaluated the effectiveness of the Communication, Information, and Education (CIE) program using the role play method to enhance knowledge about preventing sexual violence among students at An-Nabilah Islamic Middle School, Gunung Kaler District, Tangerang. The research involved 69 student respondents, with the majority being 13 years old (75.4%) and female (73.9%). The initial assessment of students' knowledge about sexual violence prevention showed an average score of 49.35, with a standard deviation of 4.105, and a range of 40 to 60. After the educational intervention, the average score significantly increased to 87.46, with a standard deviation of 4.89, and a range of 80 to 95. The improvement in scores, with a difference of 38.11, indicates a substantial enhancement in knowledge following the CIE program. The Wilcoxon test further confirmed these findings, showing a significant increase in knowledge, with an average increase of 35.00 and a sum of ranks of 2415.00 from 48 respondents. The study concludes that the CIE program using the role play method is highly effective in increasing students' knowledge about preventing sexual violence, highlighting its potential as a valuable educational tool in school settings.